The History and Development of Posterior Denture TeethÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬ÂIntroduction, Part I - Robert L. Engelmeier, DMD, MS (Journal of Prosthodontics, 2003)
THE purpose of this series of articles is to lead the reader on an intriguing journey through the historic events that led to the development and evolution of artificial teeth